Robert Nozick and Axel Honneth: An attempt to shed light on mental health service in Norway through two diametrical philosophers - Terkelsen, Toril Borch (Nursing philosophy, 2020)
This article aims at giving insight into Norwegian mental health service by exploring the ideologies of two diametrical philosophers, the American Robert Nozick (1938-2002) and the German Axel Honneth (1949-). Nozick proposes as an ideal a minimal state in which citizens have a "negative right" to the absence of interference and to follow their own interests without restriction from the state. On the other side, Axel Honneth claims that there is no freedom without state interference. In his view, governmental involvement is understood as a prerequisite for personal freedom. We may call this state an opposite of the minimal state; a maximal state. To get a better understanding of these opposite philosophies, we use texts written from conversations with people suffering from mental health problems, nurses and other caregivers in four Norwegian municipalities. Nozick's notion of the minimal state and Honneth's political philosophy of freedom and recognition were used as analytical tools. Among patients and helpers, there were different opinions about good care and how much caregivers should intervene. Some emphasized autonomy, independency, minimal involvement in human contact by nurses and other caregivers, similar a minimal state. Others perceived good care as bonding between helpers and service-users. They underlined equal and personal relationships, as well as helping with practicalities, similar a maximal state. In the discussion, we focus on how people with chronic illnesses are supposed to transform themselves into self-cared individuals, able to manage their own condition successfully with minimal help from public welfare and at a lower cost. Finally, we express concerns about who will care for disempowered patients without family and other resources in a minimal state.